2015
DOI: 10.1007/s10453-015-9399-x
|View full text |Cite
|
Sign up to set email alerts
|

Regional and seasonal variation in airborne grass pollen levels between cities of Australia and New Zealand

Abstract: Although grass pollen is widely regarded as the major outdoor aeroallergen source in Australia and New Zealand (NZ), no assemblage of airborne pollen data for the region has been previously compiled. Grass pollen count data collected at 14 urban sites in Australia and NZ over periods ranging from 1 to 17 years were acquired, assembled and compared, revealing considerable spatiotemporal variability. Although direct comparison between these data is problematic due to methodological differences between monitoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 41 publications
3
25
0
Order By: Relevance
“…Trends for grass in Australasia show that the correlation of the end date of the pollen season with average spring temperature is positive, while the same relationship for the start date is negative, suggesting also that season start dates are earlier and season duration increases with warmer climates (Medek et al, 2016). The apparent trend in the season end date for Ambrosia with PYAAT could be due to the increased number of frost-free days, consistent with global warming, and a strong relationship between frost-free days and changes of ragweed season length (Easterling 2002;Ziska et al, 2011).…”
Section: C Wozniak and A L Steiner: A Prognostic Pollen Emissiomentioning
confidence: 96%
See 1 more Smart Citation
“…Trends for grass in Australasia show that the correlation of the end date of the pollen season with average spring temperature is positive, while the same relationship for the start date is negative, suggesting also that season start dates are earlier and season duration increases with warmer climates (Medek et al, 2016). The apparent trend in the season end date for Ambrosia with PYAAT could be due to the increased number of frost-free days, consistent with global warming, and a strong relationship between frost-free days and changes of ragweed season length (Easterling 2002;Ziska et al, 2011).…”
Section: C Wozniak and A L Steiner: A Prognostic Pollen Emissiomentioning
confidence: 96%
“…Observations by Craine et al (2012) of Poaceae in an American prairie have indicated that C 3 and C 4 grass flowering occurs at distinctly different times, with C 3 in the late spring and C 4 in mid-to-late summer. Similarly, Medek et al (2016) observed two grass pollen peaks in Australia, with a stronger, late-summer peak at lower southern latitudes where there is higher incidence of C 4 grass. However, the authors note that sometimes this may be due to a second flowering of some C 3 grass species.…”
Section: Observed Seasonality Of Pollen Emissionsmentioning
confidence: 99%
“…With the exception of the Palmerston North study of pine pollen, none of these papers focused on tree pollen. Recently, a series of publications have reviewed the available information about allergenic pollen levels in Australia and New Zealand and highlighted the emphasis placed to date on grass pollen [12][13][14][15]. As such, little is known about the levels of tree pollen in New Zealand, nor the extent to which such pollens could be contributing to the burden of allergenic rhinitis in New Zealand.…”
Section: Previous Monitoring Of Airborne Pollen In New Zealandmentioning
confidence: 99%
“…GP has been identified as the leading trigger of the most severe thunderstorm‐related asthma outbreak globally, including the most recent and fatal occurring in Melbourne, Australia, in 2016, with 10 related deaths . Both temperate and subtropical grasses are found in places with diverse climatic regions such as parts of Australia, Africa, India and America (Supplementary figure 1). Research has indicated differences in allergen composition and immune recognition between the pollen of grasses from different subfamilies .…”
Section: Introductionmentioning
confidence: 99%